2018
DOI: 10.1159/000489631
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Uncomplicated Acute Diverticulitis: To Give or Not to Give?

Abstract: Acute uncomplicated diverticulitis (AUD) is generally felt to be caused by obstruction and inflammation of a colonic diverticulum and occurs in about 4-5% of patients with diverticulosis. The cornerstone of AUD treatment has conventionally been antibiotic therapy, but with a paradigm shift in the underlying pathogenesis of the disease from bacterial infection to more of an inflammatory process, as well as concerns about antibiotic overuse, this dogma has recently been questioned. We will review emerging data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Or do you mean SUDD?] has been challenged171 owing to the evolving concepts in the pathogenesis of the disease (shifting from bacterial infection to an inflammatory process), the growing concerns about antibiotic overuse and the results of several studies. Two RCTs172,173 questioned the antimicrobial use and showed that observational treatment can be considered appropriate [Au: how long was observational treatment sufficient?…”
mentioning
confidence: 99%
“…Or do you mean SUDD?] has been challenged171 owing to the evolving concepts in the pathogenesis of the disease (shifting from bacterial infection to an inflammatory process), the growing concerns about antibiotic overuse and the results of several studies. Two RCTs172,173 questioned the antimicrobial use and showed that observational treatment can be considered appropriate [Au: how long was observational treatment sufficient?…”
mentioning
confidence: 99%
“…Conservative treatment strategy without antibiotics in patients with uncomplicated AD has proven to be safe, with long‐term outcomes, in terms of recurrence, complications and need for surgery, being similar to those treated with antibiotics [ 84 , 85 , 86 , 87 , 88 ]. However, CRP level >170 mg/l is a risk factor for non‐antibiotic treatment failure [ 89 ] and selective, rather than routine, omission of antibiotics is still recommended [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although conservative treatment of AUD without antibiotics has shown to be feasible, safe, and effective [4], there is some evidence and agreement that antibiotics are still indicated in immunocompromised patients, with comorbidities as chronic kidney disease, collagen-vascular disease, diabetes, severe signs of sepsis, in patients on chronic corticosteroid therapy, or pregnant females, as these patients have a higher risk of treatment failure [4,10,11].…”
Section: Evidence Promentioning
confidence: 99%